ALTERNATIVE DISPUTE RESOLUTION IN BANYUMAS REGENCY: IN THE PERSPECTIVE OF CULTURAL STUDIES - Hudijono, Singkir; Sirtha, I Nyoman; Parimartha, I Gde; Suastika, I Made (E-Journal of Cultural Studies, 2010)
This study discusses about an Alternative Dispute Resolution in BanyumasRegency as a non-litigation dispute resolution. The problem observed was a breakthroughtaken by the Society in Banyumas Regency in overcoming the so far deadlock of lawenforcement and the attitude of not trusting the justice enforcement. It has been a publicsecret that the dispute resolutions employing the legal centralism paradigm have beendominated by the judicial network. This has caused the acknowledgement of the state lawto decrease, being a commodity that can be traded. The research aims at finding out anddescribing how the alternative dispute resolution (ADR) emerges as an alternativemechanism in deconstructing the legal centralism; interpreting and describing what ismeant by the alternative dispute resolution (ADR) in the development of progressive law.This research was conducted employing qualitative method. In this context, theresearcher explored various pieces of related information with the reason that the societyin Banyumas Regency has chosen the alternative dispute resolution mechanism as themechanism in deconstructing the legal centralism. The research was conducted asfollows: the problems were identified, the theories for analyzing the data were selected,the primary and secondary data were collected, the collected data were analyzed andinterpreted, and finally, the results of the research were written and constructed. Thetheories employed were critical legal studies, deconstruction, and large narration criticismtheories.The results of the research show that: firstly, the alternative dispute resolution hasemerged because of the awakened local knowledge, as the form of anticipation to theineffective formal law domination. With regard to the effect of global intercourse, thealternative dispute resolution has emerged because of the refusal against the culturalhomogeneity. Secondly, the implementation of the alternative dispute resolution hasbecome the preferred mechanism in deconstructing the law centralism because it can beimplemented effectively and efficiently, and ensures the win-win solution. Thirdly,denotatively, the alternative dispute solution reduces the confronting and antagonisticconceptions. Connotatively, the alternative dispute resolution is the legal culture ofBanyumas society. It has functioned as the legal dynamisator creating and implementinglaw.